VALUES OF TRANSPORTATION SUBSECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Ade Elza Surachman (SEAN Institute, 2023)
Profitability as a mediation in the influence of capital structure on the value of transportation companies on the Indonesia Stock Exchange means that companies that have a high capital structure will increase their company value if supported by a good level of profitability. In addition, profitability can also increase firm value through a mediating effect on the relationship between capital structure and firm value. The sampling technique using the purposive sampling method resulted in a sample of 23 transportation sub-sector companies on the Indonesia Stock Exchange in 2019-2021. The data analysis technique used is path analysis and moderation regression. The results showed that (1) capital structure has no significant effect on firm value, (2) profitability does not mediate the effect of capital structure on firm value, (3) profit growth strengthens the effect of capital structure on profitability.